2021
DOI: 10.1177/08902070211017760
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the hierarchical structure of the 24 VIA character strengths: Three global dimensions may suffice to capture their essence

Abstract: The Values in Action (VIA) framework maps 24 character strengths onto six more abstract virtues through a theoretical classification. However, compared to other individual difference constructs, there is little consensus about the factor-analytic structure of the VIA trait space. Applying Horn’s parallel analysis, Goldberg’s Bass-ackwards approach, and cross-country congruency analysis, we scrutinize the factor-analytic solutions-hierarchy of the 24 VIA strengths with the aim to identify one or more useful glo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 77 publications
0
19
0
1
Order By: Relevance
“…From there it inherits 50% of the items while keeping the factor structure robust. The response options are 5-point Likert-type (1 = Disagree strongly, 2 = hierarchy, which exceeds the present scope but receives attention elsewhere (e.g., Partsch et al, 2021). Previous research occasionally found that strengths form a characteristic two-factorial circular structure: a circumplex with the two axes "self-oriented" versus "other-oriented" and "head" versus "heart" (Park et al, 2017;cf.…”
Section: Scale Relationshipsmentioning
confidence: 90%
See 2 more Smart Citations
“…From there it inherits 50% of the items while keeping the factor structure robust. The response options are 5-point Likert-type (1 = Disagree strongly, 2 = hierarchy, which exceeds the present scope but receives attention elsewhere (e.g., Partsch et al, 2021). Previous research occasionally found that strengths form a characteristic two-factorial circular structure: a circumplex with the two axes "self-oriented" versus "other-oriented" and "head" versus "heart" (Park et al, 2017;cf.…”
Section: Scale Relationshipsmentioning
confidence: 90%
“…Character strengths reside at a similar level of abstraction as personality facets in the personality trait hierarchy. They form the building blocks of the VIA character trait space (McGrath et al, 2020;Partsch et al, 2021), resembling facets of traits in other trait spaces, such as the Big Five or HEXACO domains (Ashton & Lee, 2007;McCrae & John, 1992;Thalmayer & Saucier, 2014). Yet, despite these similarities, differences between the character strengths and lexically derived personality traits are evident.…”
Section: Relevance Of the Via Character Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Two decades ago, Peterson and Seligman (2004) introduced a comprehensive collection of 24 theoretically derived and empirically supported "values in action" (VIA): ubiquitously and morally valued, malleable character strengths. Locating them in a trait hierarchy, the 24 VIA character strengths are on a fine-grained level of abstraction similar to personality facets (McGrath et al, 2020;Partsch et al, 2021). That is, they are rather specific, narrow traits.…”
Section: Introductionmentioning
confidence: 99%
“…Contrariwise, there was no consensus regarding factor-analytically derived global VIA (meta-)traits 1 for a long time (see review in Partsch et al, 2021). Several recent studies, however, converge on the notion that three global metatraits can be identified in the VIA trait space.…”
Section: Introductionmentioning
confidence: 99%